The effects of Cinnamaldehyde on early brain injury and cerebral vasospasm following experimental subarachnoid hemorrhage in rabbits - (:unkn) unknown (SPRINGER/PLENUM PUBLISHERS, 2019)
The neuroprotective and vasodilatory effects of cinnamaldehyde have been widely studied and documented. On the basis of these findings, we hypothesized that cinnamaldehyde exhibits therapeutic effects on subarachnoid hemorrhage-induced early brain injury and cerebral vasospasm. Thirty-two adult male New Zealand white rabbits were randomly divided into four groups of eight rabbits: control, subarachnoid hemorrhage, subarachnoid hemorrhage + vehicle, and subarachnoid hemorrhage + cinnamaldehyde. An intraperitoneal dose of 50 mg/kg cinnamaldehyde was administered 5 min following an intracisternal blood injection, followed by three further daily injections at identical doses. The animals were sacrificed 72 h after subarachnoid hemorrhage was induced. The cross-sectional areas and arterial wall thicknesses of the basilar artery were measured and hippocampal degeneration scores were evaluated. Treatment with cinnamaldehyde was effective in providing neuroprotection and attenuating cerebral vasospasm after subarachnoid hemorrhage in rabbits. It effectively increased the cross-sectional areas of the basilar artery and reduced the arterial wall thickness; in addition, hippocampal degeneration scores were lower in the cinnamaldehyde group. The findings of this study showed, for the first time to our knowledge, that cinnamaldehyde exhibits neuroprotective activity against subarachnoid hemorrhage-induced early brain injury and that it can prevent vasospasm. Potential mechanisms underlying the neuroprotection and vasodilation were discussed. Cinnamaldehyde could play a role in subarachnoid hemorrhage treatment.
Keywords: Cinnamaldehyde; Early brain injury; Neuroprotection; Rabbit; Subarachnoid hemorrhage; Vasospasm; REDUCING OXIDATIVE STRESS; ROOT GANGLION NEURONS; KAPPA-B; POTENTIAL CONTRIBUTION; TRANS-CINNAMALDEHYDE; CALCIUM-CHANNELS; RAT; MECHANISMS; ACTIVATION; REDUCTION